1977
DOI: 10.1111/j.1365-2230.1977.tb01533.x
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary trichilemmal cysts. HEREDITARY PILAR CYSTS

Abstract: Summary One hundred and fifteen individuals from 60 families are described who had trichilemmal cysts. These were solitary or multiple intradermal cysts and occurred most frequently on the scalp. A punctum leading from the skin surface to the cyst was not seen in any patient. Because they are encapsulated they are easily removed. Histologicaily they resemble the external root sheath in the region of the follicular isthmus and are quite different from epidermoid cysts. They are not associated with Gardner's syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 14 publications
1
37
0
Order By: Relevance
“…It occurs predominantly on the scalp [McGavran and Binnington, 1966;Pinkus, 1969], is easily enucleated and appears as a firm, smooth, whitewalled cyst without a punctum [Leppard and Sanderson, 1976;Leppard et al, 1977]. Benign, relatively uncommon, invasive proliferating trichilemmal tumors [Naik et al, 1990;Hendricks et al, 1991;Laing et al, 1991;Reis et al, 1993;Sleater et al, 1993] and rare cases of metastasizing proliferating trichilemmal cysts [Weiss et al, 1995;Park et al, 1997] have been reported.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…It occurs predominantly on the scalp [McGavran and Binnington, 1966;Pinkus, 1969], is easily enucleated and appears as a firm, smooth, whitewalled cyst without a punctum [Leppard and Sanderson, 1976;Leppard et al, 1977]. Benign, relatively uncommon, invasive proliferating trichilemmal tumors [Naik et al, 1990;Hendricks et al, 1991;Laing et al, 1991;Reis et al, 1993;Sleater et al, 1993] and rare cases of metastasizing proliferating trichilemmal cysts [Weiss et al, 1995;Park et al, 1997] have been reported.…”
Section: Introductionmentioning
confidence: 97%
“…Benign, relatively uncommon, invasive proliferating trichilemmal tumors [Naik et al, 1990;Hendricks et al, 1991;Laing et al, 1991;Reis et al, 1993;Sleater et al, 1993] and rare cases of metastasizing proliferating trichilemmal cysts [Weiss et al, 1995;Park et al, 1997] have been reported. This is an autosomal dominant trait [Leppard et al, 1977], but it does not yet have its separate entry in the OMIM database. In this study we report assignment of the first locus for TRICY1 and mutation screening data on two candidate genes, CTNNB1 and MHL1.…”
Section: Introductionmentioning
confidence: 99%
“…10,13,34 Trichilemmal cysts differ from epidermoid cysts in that they do not have an overlying punctum and they rarely become inflamed. 16,30 Certain reports in the literature suggest and describe findings seen in certain imaging or cytologic studies done for this pathology. These studies are suggested whenever a malignant degeneration is suspected by history and physical examination or for differential diagnosis with other pathologies or more serious entities such as meningocele or enphalocele.…”
Section: Differential Diagnosismentioning
confidence: 95%
“…Several reports in the literature about trichilemmal cysts have been written describing the natural history and nomenclature 19,30 ; the ultrastructural, cytologic, and histologic description 15,31Y36 ; the hereditary component 5 ; the potential of transformation into a proliferating trichilemmal cysts or malignant degeneration 4,14Y16,20Y22,27,29 ; the surgical techniques for removal 15,37,38 ; the imaging modalities for diagnosis 39 ; and the unusual presentations in several case reports. 6,40Y42 More than 60 of these published studies were reviewed.…”
Section: Differential Diagnosismentioning
confidence: 97%
“…1 In lesions that are not inflammed and small, simple extraction is usually performed through the use of a small overlying elliptical incision or through access using a 3 mm to 4 mm punch. 2 Larger cysts, especially those greater than 1.5 cm to 2.0 cm, often act as tissue expanders, creating overlying skin redundancy requiring removal in order to achieve a smooth contour.…”
mentioning
confidence: 99%